Implementation of Dynamic Capability in Culinary MSMEs: A Case Study of Kedai Suho, Bandar Lampung - Dea Uswatun Hasanah; Icha Nur Fadilnia; M. Gibran Yudha; Vicky F Sanjaya M.Sc (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the implementation of dynamic capability in culinary SMEs, particularly Kedai Suho, in responding to market changes, customer needs, and operational challenges. The study employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation related to Kedai Suho's operations. The results indicate that Kedai Suho applies three dimensions of dynamic capability: sensing, seizing, and reconfiguring. The owner demonstrates sensing capability by identifying changes in customer preferences through menu innovation and topping variations. Seizing capability is reflected in strategies such as menu diversification, promotions, and customer-oriented service to enhance loyalty. Reconfiguring capability is implemented through improvements in raw material quality, packaging, and food presentation. Despite stable business performance, significant challenges arise from digital platform fees and taxes, affecting profit margins. This study recommends strengthening digital adaptation strategies, systematic financial management, and continuous innovation to maintain competitiveness and business sustainability.